A genetic approach reveals different modes of action of prefoldins. Issue 3 (23rd July 2021) - Blanco-Touriñán, Noel; Esteve-Bruna, David; Serrano-Mislata, Antonio; Esquinas-Ariza, Rosa María; Resentini, Francesca; Forment, Javier; Carrasco-López, Cristian; Novella-Rausell, Claudio; Palacios-Abella, Alberto; Carrasco, Pedro; Salinas, Julio; Blázquez, Miguel Á; et al.
Abstract: The prefoldin complex (PFDc) was identified in humans as a co-chaperone of the cytosolic chaperonin T-COMPLEX PROTEIN RING COMPLEX (TRiC)/CHAPERONIN CONTAINING TCP-1 (CCT). PFDc is conserved in eukaryotes and is composed of subunits PFD1–6, and PFDc-TRiC/CCT folds actin and tubulins. PFDs also participate in a wide range of cellular processes, both in the cytoplasm and in the nucleus, and their malfunction causes developmental alterations and disease in animals and altered growth and environmental responses in yeast and plants. Genetic analyses in yeast indicate that not all of their functions require the canonical complex. The lack of systematic genetic analyses in plants and animals, however, makes it difficult to discern whether PFDs participate in a process as the canonical complex or in alternative configurations, which is necessary to understand their mode of action. To tackle this question, and on the premise that the canonical complex cannot be formed if one subunit is missing, we generated an Arabidopsis ( Arabidopsis thaliana ) mutant deficient in the six PFDs and compared various growth and environmental responses with those of the individual mutants. In this way, we demonstrate that the PFDc is required for seed germination, to delay flowering, or to respond to high salt stress or low temperature, whereas at least two PFDs redundantly attenuate the response to osmotic stress. A coexpression analysis of differentially expressed genes in the sextuple mutant identified several transcription factors, including ABA INSENSITIVE 5 ( ABI5 ) and PHYTOCHROME-INTERACTING FACTOR 4, acting downstream of PFDs. Furthermore, the transcriptomic analysis allowed assigning additional roles for PFDs, for instance, in response to higher temperature. Abstract : Prefoldins contribute to Arabidopsis growth and response to the environment through mechanisms that are dependent on or independent of the canonical prefoldin complex.